In vivo induction of normal differentiation in myeloid leukemia cells - Lotem, Joseph (1978)
MGI(+)D(+), MGI(+)D(-), and MGI(-)D(-) mouse myeloid leukemic cells, which genetically differ in their competence to be induced to undergo normal cell differentiation in vitro by the normal macrophage- and granulocyte-inducing protein MGI, were analyzed for their ability to undergo cell differentiation in diffusion chambers in vivo. As after induction by MGI in vitro, MGI(+)D(+) clones were induced for Fc and C3 rosettes, lysozyme, and mature macrophages and granulocytes in normal syngeneic or allogeneic mice. MGI(+)D(-) clones were also induced in these mice for all these properties, although in vitro they were not induced by MGI for mature cells. The MGI(-)D(-) clones were induced in vivo for C3 and Fc rosettes, lysozyme, and intermediate stages but not for mature cells, whereas none of these properties were induced in these clones by MGI in vitro. Thus, certain types of myeloid leukemic cells differentiate better in vivo, possibly due to the presence of higher effective concentrations of MGI and/or other inducing factors, and MGI(+)D(+) and MGI(+)D(-) cells can completely differentiate in vivo to mature cells. In vivo differentiation was inhibited in mice treated with cyclophosphamide. It was also inhibited in various strains of nude mice, except for one MGI(+)D(+) clone, where it was inhibited in C57BL/6 but not in ICR nude mice. This MGI(+)D(+) clone was also the only clone that was induced to differentiate normally in vitro by a 23,000 molecular weight form of purified MGI. The results suggest that different clones respond to different molecular forms of MGI, which may be present in different proportions in some animals, that in vivo differentiation by MGI possibly with other factors may be regulated by cells involved in the immune response, and that this differentiation can be genetically controlled. Differentiation in vivo was enhanced by injection of conditioned medium containing MGI and by inoculation of MGI-producing cells, including normal granulocytes. This indicates that the induction of normal differentiation of myeloid leukemic cells in vivo can be enhanced by these treatments.